The Organizational and determinant model of the educational cluster of a Higher Education Institution - I. Khramtsova, Flura (2020)
Strategies for sustainable economic growth of national states make the problem of training highly qualified personnel important in the cluster infrastructure of a higher education institution. The organizational and determinant model of the educational cluster “high school-higher education institution-science” devised in the course of the study is capable of influencing the level of academic continuity as the main mechanism for the reproduction of scientific personnel to solve modernization problems. In the course of the study the following methods were used: comparative analysis, content analysis, generalization, classification, synthesis, extrapolation, design and modeling. The authors of the paper have developed the concept of academic mobility of students under the conditions of the educational cluster “high school-higher education institution-science”. The methodology of the individual cluster follow-up and support for students has been substantiated scientifically. The results were tested in the research and educational activities of the affiliate of Russian State Social University in the city of Minsk, the Republic of Belarus, in the State Educational Institution “High school No. 1 of Minsk named after Francis Skorina”, the State Educational Institution “Grodno City High School”. The prospects for further research consist in developing the institutional foundations of cluster mechanisms for the union integration of science, higher and secondary education institutions of the Republic of Belarus and the Russian Federation. Innovative ideas of the clustering policy of higher education institutions in the framework of the Union State require informational support, the use of the resources of the Public Chamber of the Union State, the Russian Center for Science and Culture, and business communities of Belarus and Russia.